KOMPARASI PANDANGAN FILSAFAT AGAMA ALBERT EINSTEIN DAN HOLMES ROLSTON III - Krisna Suksma Yogiswari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
The effort of searching God that be done by human, some of them really find God but also many of them that be lost in the forest of Metafisisme. The discussion of philosophy and religion is the case that very interesting, even many philosophy which has been discussed about them, start from the contra until want to join both of them. In the case the contribution of philosophy and sciences is to accompany of faith to the God, within certain limits can support the various evidence of the truth of existence and the power of God which has been widely revealed by religion. Science seek the truth by research, experience (empirical) and experiment as the exam. Philosophy approache the truth with exploration of common sense in radical (rooted), it does not feel bound by any, expect by their own hands, that is logic. This study will compare the ideas of Albert Einstein and Holmes Rolston III who use the approach of science in studying the philosophy of religion.